A BIBLIOMETRIC ANALYSIS OF 68 YEARS OF RESEARCH ON CHARITABLE GIVING - Aqilah Yaacob; Gan Jen Ling (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This is the first study, to the authors’ knowledge, to evaluate and quantify the progress of charitable giving as there is no research on the global trend of charitable giving. This research aimed to retrieve journal articles related to charitable giving over a 68-year time span and suggest new avenues for future research. This study involved a bibliometric analysis from 1,144 publications related to the theme, registered in the Scopus database from 1951 to the recent publication in 2019. The bibliometric procedures examined the research performance and development within the framework of international impact, while VOS Viewer 1.6.11 visualized the overall research trend of charitable giving. The results indicate that the United States is the country with the most publications related to charitable giving. James, R.N. and List, J.A. are the two leading authors in this field based on the total number of publications. Most of the articles published in this field are found in Non-profit and Voluntary Sector Quarterly, Journal of Public Economics, and Voluntas journals. While Journal of Business Research and Journal of Consumer Research are the top two leading CiteScore journals in charitable giving studies. Among the most recent author keywords are crowdfunding, social media, social status, social preferences, emotion, incentives, agency, and laboratory experiment, which demonstrated the current keen interest associated with charitable giving studies. This paper is beneficial for academicians, organizations, and policymakers in understanding the general picture of the field and enables future scholars to see where the study began and trace its shift over time.